Comparative evaluation of compressive strength of three restorative materials employed in pediatric dentistry - Ramírez Báez, Raquel (2022)
Objective: The aim of this in vitro comparative study was to compare the compressive strength of three different filling restorative materials that are frequently used in pediatric dentistry. Materials and methods: A total of 270 specimens (n=90 per group) of Cention N®, EQUIA Forte® Fil, and Riva Light Cure HV® were prepared following the manufacturer's instructions. The compressive strength was tested using a crosshead speed of 0.75±0.30 mm/min along the long axis of the specimens by means of a universal test machine. The tests were performed on the specimens after 24, 48, and 72h of storage at 37ºC, with a relative air humidity of 50±10%. Data were statistically analyzed using the one-way ANOVA and Kruskal-Wallis tests. Results: After the three periods of evaluation, Cention N® exhibited higher mean values (166.2±36.3 MPa at 24h, 153.8±40.2 MPa at 48h and 167.3±36.2 MPa at 72h) than EQUIA Forte® Fil and Riva Light Cure HV® (p<0.05). Between EQUIA Forte® Fill and Riva Light Cure HV® there was no significant difference (p>0.05). Compressive strength values increased only in EQUIA Forte® Fil with no significant difference after 24, 48 and 72 h. Conclusions: Cention N® showed the highest compressive strength values after 24, 48 and 72h of storage, which means that it can provide better clinical performance and mechanical behavior.